Early acetaminophen administration and mortality outcomes in critically ill patients with cirrhosis: a retrospective analysis from the MIMIC-IV database - Xiao-fei Fan; Shao-kang Xu; Shen-ao Fu; Xuan He; Jia-kai Fang; Wen Gao; Na Guo (BMC Gastroenterology)
Abstract Background Cirrhosis is a major global health burden, often requiring ICU admission due to complications. Acetaminophen (APAP) is frequently used for pain and fever management in critically ill patients, but its safety in cirrhotic patients remains uncertain. Aims To evaluate the association between early APAP use and mortality outcomes in ICU patients with cirrhosis. Methods This retrospective cohort study used the MIMIC-IV database. Adult cirrhotic patients were divided into two groups based on whether they received APAP within 24 h of ICU admission. The primary outcome was 28-day ICU mortality; secondary outcomes included 7-day, 60-day, in-hospital, and overall ICU mortality. Inverse probability weighting (IPW) was used to adjust for confounders. Results After IPW adjustment, early APAP use was significantly associated with higher 28-day ICU mortality (HR: 1.70, 95% CI: 1.26–2.3), and elevated risks for all secondary outcomes. Subgroup analyses indicated higher mortality risks in patients with cancer, AKI and sepsis. Total bilirubin levels were identified as a potential predictor of mortality risk. Conclusions Early APAP administration in critically ill cirrhotic patients is associated with increased mortality. These findings underscore the need for caution when prescribing APAP in this high-risk population and highlight the importance of further prospective validation.